Asking Why: Towards Conscious Decision-making in times of VUCA - Steffen, Barbara (Electronic Communications of the EASST, 2022)
To ensure an organization’s long-term success in times of vulnerability, uncertainty, complexity and ambiguity it is fundamental that organizations focus on continuous adaptation. The key to success is to understand why to adapt and what to achieve to ensure that all initiatives and measures achieve new internal and/or external value for the organization. Today, digitalization gets simultaneously perceived as threat and opportunity. One problem is that digitalization is not clearly defined and thus intangible. However, established organizations must be careful to not mistake digitalization as a goal in itself. Just adopting IT-tools does not lead to success. Thus, the from Digital Vagueness to Aligned, Lifelong Understanding and Evaluation Canvas (Digital V ALUE Canvas) aims to support and guide organizations in identifying, designing and implementing value-driven solutions. To ensure the value proposition’s uniqueness and competitiveness it is key that it is built on the organization’s strengths and enabled by today’s digital possibilities.